بنية الكلمة ودورها في تعليم اللغة العربية للناطقين بغيرها وفهم معانيها: The Structure of the Word and Its Role in Teaching Arabic Language to Speakers of Other Languages and Understanding Its Meanings - Abdul Maqsud, Mohammad Aziz; Mohammad al-Baz, Mohammad Radhi (Journal of Islamic Educational Research, 2020)
This is a conceptual paper on the structure of the word as word has many unique and influential contexts. Some classical and modern linguists try to link the building of words with its meanings, and then comes role of the context of all patterns in showing these meanings. Sometimes the context of the meaning can be accepted by some structures and not others, which shows that the premise in the word structure have a significant role in understanding the meanings, and that change leads to variety contributions in upgrading the learners of the Arabic language for non-native speakers.